Assessing Occupational and Recreational Noise Levels during National Hockey League Games and its Impact on Employees and Attendants - Curtis, Samantha (East Carolina University)
Workers and attendees of sporting events can be exposed to harmful levels of noise during the event, potentially affecting hearing This study assessed the noise exposure of workers and attendees at 12 National Hockey league games at PNC arena in Raleigh, North Carolina. Nine employees were placed on various arena levels while wearing noise dosimeters, with one dosimeter placed in an office in the arena for area noise monitoring. A sound level meter was also placed in a fixed location on the lowest arena level. The employees were recruited by email, and during meetings before the game. The noise levels were compared between rival and non-rival games, and between arena levels. The results from the sound level meter showed that the highest average noise level was at Game 1 (89.2 ± 5.3 dBA), while the lowest average was at Game 4 (83.2 ± 7.4 dBA), both of which were non-rival games. The results from personal monitoring showed that Game 1 (88.1 ± 2.0 dBA), Game 4 (85.1 ± 2.7 dBA), and Game 12 (85.1 ± 5.9 dBA) had 8-hr TWAs exceeding the ACGIH TLV of 85 dBA. It also showed that the 8-hr TWAs in all the games did not exceed the OSHA PEL of 90 dBA. The 8-hr TWAs for non-rival games for both ACGIH and OSHA PEL (83.6 ± 2.6 dBA and 76.4 ± 3.6 dBA, respectively) were not significantly different (t= -0.72, p=0.48 and t= -1.26, p=0.21, respectively) from those of rival games (83.0 ± 1.8 dBA and 75.1 ± 2.0 dBA, respectively). The greatest difference between the rival and non-rival games was observed on the noise dose% for both OSHA PEL and ACGIH, with the OSHA noise dose% of 19.2% for non-rival games and 15.4% for rival games. Moreover, the ACGIH noise dose% for the non-rival games was 98.5% and that of the rival games was 89.7%. However, such differences for both ACGIH and OSHA PEL noise doses were not significant (t= -0.47, p=0.64 and t= -1.34, p=0.18, respectively). The ACGIH Lavg for the non-rival games (90.1 ± 2.0 dBA) was not significantly different (t= -0.81, p=0.42) from that of the rival games (89.6 ± 1.4 dBA). Similarly, the OSHA PEL Lavg for the rival games (81.7 ± 1.6 dBA) was not significantly different (t= -1.39, p=0.17) from that of the non-rival games (82.9 ± 3.0 dBA). Level 2 of the arena had the highest ACGIH Lavg of 91.1 ± 5.8 dBA. The office has the lowest ACGIH Lavg (86.5 ± 1.7 dBA). The ACGIH TWA for the office was 79.4 ± 3.7 dBA. For the OSHA PEL, level 1 has the highest Lavg level of 83.9 ± 3.9 dBA and a TWA of 77.4 ± 4.4 dBA. The office level was the lowest OSHA PEL Lavg of 76.4 ± 4.1 dBA and the lowest TWA of 69.3 ± 6.1 dBA. Level 2 had the highest maximum noise level of 106.7 ± 6.8 dB while the office had the lowest maximum level of 100.5 ± 3.2 dB. Findings of this study will be beneficial to identify recommended controls for noise exposure for workers and attendees, such as worker rotation and wearing hearing protection.
Keywords: exposure assessment; recreation; occupational exposure; Arenas--North Carolina--Raleigh--Noise; Industrial hygiene--North Carolina--Raleigh; Hockey--North Carolina--Raleigh--Noise; National Hockey League